(untitled) (مجلة إحالات, 2026)
We will present in this paper our personal reading about the genetic structural approach as adopted and applied by the Algerian critic, ‘Mokhtar Habbar’, in his book entitled (či’r abi medyen ‘tilimsani: ‘eru’ya wa tečkil), litrally: ‘The Poetry of Abi Mediyen Al-Tilimsani, Vision and Formation’, we outlined this research into two parts. We devoted the first part the definition of the concepts and the objectives of the approach as stated by Lucien Goldman, and consecrated the second part to ‘Mokhtar Habbar’ analysis.